Looking towards the sweet, sweet future: a political economy analysis of sugar and nutrition policy in Indonesia - Ellen Johnson; Hafizah Jusril; Liza Pratiwi; Suci Trisnasari; Anne Marie Thow; Cut Novianti Rachmi (Public Health Nutrition)
Abstract